Grupo folclórico por el festival regional libro - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: La fotografía muestra la participición musical de un grupo folclórico de la amazonía peruana en el festival regional del libro.
ENGLISH: The photograph shows the musical participation of a folkloric group from the Peruvian Amazon at the regional book festival.

SPANISH: La fotografía muestra la participición musical de un grupo folclórico de la amazonía peruana en el festival regional del libro.
ENGLISH: The photograph shows the musical participation of a folkloric group from the Peruvian Amazon at the regional book festival.
Folkloric group for the regional book festival
Keywords: Iquitos (Perú)|~|Actividades culturales|~|Perú|~|Perú--Cultura Amazónica|~|Perú--Personajes Religiosos